A case of Streptococcus cristatus infective endocarditis mimicking anti-neutrophil cytoplasmic antibody associated vasculitis - Shahab, Aliya; C. N., Arunraj; Legha, R.; Sadar, Aarsha (International Journal of Research in Medical Sciences, 2025)
We report a case of a 55-year-old female presenting with infective endocarditis caused by Streptococcus cristatus (S. cristatus) along with c-anti-neutrophil cytoplasmic antibody (ANCA) positivity. S. cristatus is an infrequent cause of infective endocarditis with only 6 reported cases. ANCA positivity is rare in infective endocarditis. In our case ANCA positivity had the potential to mislead towards an autoimmune etiology, but the positive test was eventually understood to be caused by the S. cristatus infection. Our case also had unusual presentations like erythema nodosum and thrombotic events. This case also adds scientific literature on the capacity of Streptococcus cristatus to produce serious infections like endocarditis.